Perencanaan Pendidikan Karakter - Nurmarito Rambe; Mhd. Joni Marpaung; Inom Nasution (Departement of Mathematics Education, 2024)
A key consideration in educational planning is how students' attitudes and values develop. Curriculum and activities that foster social skills, ethics and values such as responsibility, honesty and respect will be part of a well-planned program. Character education should be planned through the stages of knowledge, application, and habituation. Education plays an important role in shaping people's personalities, behaviors, and mindsets as well as improving culture in the future. This research is literature-based with a desk research component. Data collection involves information from various literature sources, not only limited to books, but also including magazines, materials and other research. The main focus of desk research is to find various theories, laws, arguments, principles, opinions, ideas and other materials that can be used to examine and solve the problem under study. The conclusion of this research is that character education planning must be done immediately to foster the next generation of the nation. Through the use of these character-building elements, the goals of the national education system will be achieved.